Basic health physics : problems and solutions - Bevelqcqua, Joseph John (John Wiley & Sons, 1999)
Radiation litigation, the cleanup and decommissioning of nuclear facilities, radon exposure, nuclear medicine, food irradiation, stricter regulatory climate—these are some of the reasons health physics and radiation protection professionals are increasingly called upon to upgrade their skills. Designed to prepare candidates for the American Board of Health Physics Comprehensive examination (Part I) and other certification examinations, Basic Health Physics: Problems and Solutions introduces professionals in the field to radiation protection principles and their practical application in routine and emergency situations. It features more than 650 worked examples illustrating concepts under discussion along with an in-depth coverage of sources of radiation, standards and regulations, biological effects of ionizing radiation, instrumentation, external and internal dosimetry, counting statistics, monitoring and interpretations, operational health physics, transportation and waste, nuclear emergencies, and more. Reflecting for the first time the true scope of health physics at an introductory level, Basic Health Physics: Problems and Solutions gives readers the tools to properly evaluate challenging situations in all areas of radiation protection, including the medical, university, power reactor, fuel cycle, research reactor, environmental, non-ionizing radiation, and accelerator health physics.
Keywords: radiační ochrana; Radiometry; Physics; Radiation Protection; fyzika; fyzika, biofyzika; radiometrie